Co-construction de sens en situation de conception d ’un outil didactique - Brassac, Christian; Grégori, Nicolas (Studia Romanica Posnaniensia, 2007)
In the article, the author defends a thesis on the necessity of application in psychology and other cognitive sciences of a methodology based on the interactive theory. Therefore, it is postulated that analysis from the perspective of a monologue be replaced by the analysis from the interactive perspective. The article consists of two parts. In the first part a model of mutual understanding is presented, which was devised at the Psychological Laboratory of the Nancy University 2, and in the other, a proposal of application of this model for the developing of didactic aids of a multimedial character is discussed.